Infiltrative solid papillary carcinoma of the breast with axillary lymph node metastasis: a case report - Xiaowei Zhang; Bifei Huang; Kangbin Wu; Saiping Fu (BMC, 2023)
Abstract Background Solid papillary carcinoma (SPC) is a rare breast papillary tumor variant. The main histological features of SPC consist of neoplastic cell-rich nodules with thin fibrovascular cores, often accompanied by mucous secretion and neuroendocrine differentiation. Infiltrative solid papillary carcinoma (ISPC) tumor cells have an invasive, map-like growth pattern with serrated irregular growth. Due to its unique clinicopathological features, SPC is classified as two pathological tissue types based on the 2019 WHO classification of breast tumors: SPC in situ and ISPC. Case presentation We report a case of a 55-year-old female patient who was admitted to the hospital due to a painless left breast mass that had persisted for two years. Mammography suggested a mass in the left upper outer quadrant (BI-RADS 4B), and ultrasound of the breast demonstrated a cystic mass of the left breast (US_BI_RADS 4 C) with multiple enlarged lymph nodes in the left axilla. Postoperative pathology revealed ISPC with one lymph node metastasis in the left breast. Modified radical mastectomy was performed on the left breast. Subsequently, the patient received letrozole endocrine therapy, epirubicin hydrochloride and cyclophosphamide chemotherapy, and radiotherapy of the left chest wall and left upper and lower clavicular regions. After 17 months of follow-up, there was no evidence of recurrence or distant metastasis. Conclusions SPC is a group of heterogeneous tumors. SPC in situ has a good prognosis. In contrast, ISPC has a unique histological morphology and growth pattern with invasive biological behavior that can lead to lymph node and distant metastases.